2001
DOI: 10.1097/00000478-200101000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of Barrett's Esophagus and Intestinal Metaplasia of the Distal Esophagus and Gastroesophageal Junction

Abstract: The pathogenesis of short segment Barrett's esophagus (SSBE) and intestinal metaplasia (IM) of the gastroesophageal junction (IMGEJ) are poorly understood. Also, these conditions are difficult to distinguish from one another based solely on endoscopic and pathologic criteria. Therefore, the aim of this study was to evaluate the immunophenotypic features of SSBE and IMGEJ and to compare the results with lesions of known etiologies: long segment BE (LSBE) caused by reflux disease and Helicobacter pylori-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
114
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 30 publications
8
114
1
2
Order By: Relevance
“…32 This has been confirmed by several independent studies. [33][34][35][36][37][38][39] Furthermore, mAbDas-1 can detect colonic metaplasia before the histological appearance of BE, suggesting the existence of a 'Pre-Barrett's' stage. 34,35 The data suggest that expression of CEP preceded histological BE and persisted during development of metaplasia and progression to carcinoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…32 This has been confirmed by several independent studies. [33][34][35][36][37][38][39] Furthermore, mAbDas-1 can detect colonic metaplasia before the histological appearance of BE, suggesting the existence of a 'Pre-Barrett's' stage. 34,35 The data suggest that expression of CEP preceded histological BE and persisted during development of metaplasia and progression to carcinoma.…”
mentioning
confidence: 99%
“…CK8/18 has been observed in multi-layered epithelium in BE by immunocytochemistry. 51 This focal multi-layered epithelium within BE comprises cells that concurrently express both squamous and columnar cytokeratin markers, much like the esophageal mucosal gland duct epithelium 34 and the non-neoplastic telomerase-immortalized Barrett's cell line, (BAR-T). 52 We utilized the BAR-T cell line as a model to identify the specific cell phenotype in a heterogeneous 52 cell population that could demonstrate molecular and/or cell phenotypic changes following chronic exposure to acid and bile.…”
mentioning
confidence: 99%
“…Some subsequent studies appeared to reproduce these findings (19,25,30,31) . However, other authors presented discordant results and they concluded that these patterns are not useful to differentiate BE from intestinal metaplasia of the cardia (6,7,13,20,21,27) . In spite of these inconsistencies, these studies produced some outcomes that deserve further consideration.…”
Section: Discussionmentioning
confidence: 99%
“…MOHAMMED et al (21) identified the Barrett pattern in 55% of biopsies from inflamed or normal cardiac mucosa without evidence of intestinal metaplasia. GLICKMAN et al (13) noted that the immunophenotypes of the cardiac mucosa in patients with long-segment BE, shortsegment BE and normal esophagogastric junction were similar for Das-1 and CK7/CK20, but they were different from those of the gastric antral mucosa. DeMEESTER et al (6) observed that the cardiac mucosa showed the Barrett pattern in 85% of their cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation